The Effect of Bait Type on Total Catch of Skipjack Tuna (Katsuwonus Pelamis) by Using Hand Line - Larengka, Falenscya; Manoppo, Lefrand; Manu, Lusia; Sitanggang, Effendi P.; Luasunaung, Alfred; Kayadoe, Mariana E. (Jurnal Ilmiah Platax, 2022)
A hand line is one type of fishing gear that is often used by traditional fishermen to catch fish. Hand lines are categorized as active fishing gear and are also environmentally friendly. The operation of the equipment is relatively simple, it does not use a lot of auxiliary equipment such as fishing trawls and ring trawls.  This research was conducted in March and April 2022 in the Alo village, District Rainis, Talaud Islands Regency. The purpose of this study was to determine the best type of bait for catching skipjack tuna (Katsuwonus pelamis) with hand lines and to identify other types of fish caught. The method used in this research is a descriptive and participatory method, namely collecting data on catches in the fishing ground. Data analysis used a Randomized Block Design. The three types of bait used are artificial bait (silk), live fish bait, and chicken feathers. During this research, totally caught as many as 57, that is skipjack tuna (Katsuwonus pelamis) 31 (54.39%), mackerel tuna (Euthynnus affinis) 17  (29.82%), and mahi-mahi (Coryphaena hippurus) 9 (15.79). Based on the data analysis, the treatment of the type of hand line bait did not affect to catch.Keywords: skipjack; hand line; bait; catch. Abstrak        Pancing ulur merupakan salah satu jenis alat penangkapan ikan yang sering digunakan oleh nelayan tradisional untuk menangkap ikan di laut dan termasuk alat penangkapan ikan yang aktif dan juga ramah lingkungan. Penelitian ini dilakukan pada Maret dan April 2022 di desa  Alo, Kecamatan Rainis, Kabupaten Kepulauan Talaud. Tujuan penelitian adalah mengetahui jenis umpan yang terbaik untuk menangkap ikan cakalang (Katsuwonus pelamis) dengan pancing ulur dan mengetahui jenis ikan lainnya yang tertangkap.  Metode yang digunakan adalah metode deskriptif dan partisipatif, yaitu pengambilan data hasil tangkapan di daerah penangkapan (fishing ground). Analisis data menggunakan Rancangan Acak Kelompok.Tiga jenis umpan yang digunakan adalah umpan tiruan (kain sutera), umpan ikan hidup dan bulu ayam. Selama penelitian, total ikan yang tertangkap sebanyak 57 ekor ikan yang terdiri dari cakalang (Katsuwonus pelamis) sebanyak 31 ekor (54,39%), tongkol (Euthynnus affinis) sebanyak 17 ekor (29,82%) dan lemadang (Coryphaena hippurus) sebanyak 9 ekor (15,79%). Berdasarkan analisis data, perlakuan jenis umpan pancing ulur tidak berpengaruh terhadap hasil tangkapan.Kata kunci : cakalang, pancing ulur, umpan dan hasil tangkapan.